Generating Comprehensible Summaries of Rushes Sequences based on Robust Feature Matching - Truong, Ba; Venkatesh, Svetha (Association for Computing Machinery, Inc. (ACM), 2007)
This paper describes our first attempt at tackling a pilot task in Trecvid: video summarization of rushes data [3]. Our method is based on the tight clustering produced via SIFT matching. In this first attempt, we try to examine how our approach performs without complex implementation in terms of concept detection and excerpt assembly (i.e, no picture-in-picture, split screen and special transitions). Although we do not perform very well in terms of concept inclusion, we rank very well in terms of the summary being easy to understand and relevancy of included segments.